TRANSRECTAL ULTRASOUND GUIDED BIOPSY OF THE PROSTATE - Jafri, S. Saleem A.; Ahmed, M.; Husain, S.; Khan, F.A. (Journal of Ayub Medical College Abbottabad, 1998)
Transrectal ultrasonography is a useful method of imaging the prostate gland. Endorectal ultrasonography may be used in the assessment of the enlarged or nodular prostrate. Benign prostatic hyperplasia, prostatitis and prostatic cancer can be evaluated by this technique. In the management of patients with prostatic cancer, transrectal ultrasound scanning is invaluable in the diagnosis, staging, treatment and follow-up of the disease. We at Jinnah Hospital/Lahore General Hospital Lahore are using this technique for the imaging of prostate for the last many years. In this paper we will describe our experience regarding the value of transrectal ultrasound guided biopsy of the prostate in the diagnosis of prostatic cancer. A consecutive series of 200 ultrasound-guided biopsies of the prostate have been analysed. In 121 patients, in whom malignancy was suspected by both digital examination and ultrasound, 72 cancers were confirmed histologically. In 33 patients in whom digital rectal examination suggested cancer but ultrasound was normal, 3 cancers were confirmed. In 30 patients with a normal digital examination but a suspicious ultrasound appearance, 5 cancers were proven. Key Words: Transrectal ultrasonography of the prostate; Prostatic biopsy; Imaging of the prostate by ultrasound.